Acid Suppression Does Not Improve Laryngomalacia Outcomes but Treatment for Oropharyngeal Dysphagia Might Be Protective - Duncan, Daniel R.; Larson, Kara; Davidson, Kathryn; Williams, Nina; Liu, Enju; Watters, Karen; Rahbar, Reza; Rosen, Rachel L. (The Journal of pediatrics, 2021)
To determine whether the use of acid suppression and thickened feeds impact laryngomalacia outcomes in infants, including supraglottoplasty risk, time to supraglottoplasty, and hospitalization risk. We performed a retrospective cohort study to compare risk and time with supraglottoplasty and frequency and duration of hospitalizations for infants diagnosed with laryngomalacia at Boston Children's Hospital between January 1 and December 31, 2017. The primary outcomes were supraglottoplasty requirement, time to supraglottoplasty, and hospitalization risk. Multivariate analyses were performed to determine predictors of supraglottoplasty and hospitalization risk after adjusting for laryngomalacia severity and comorbidities in addition to propensity score adjustment. Kaplan–Meier curves were created to determine the impact of acid suppression use on time to supraglottoplasty. In total, 236 subjects with mean age 62.6 ± 4 days were included in the analysis; 55% were treated with acid suppression. Subjects treated with acid suppression had a greater risk of supraglottoplasty (hazard ratio 3.36, 95% CI 1.36-8.29, P = .009), shorter time to supraglottoplasty (5.64 ± 0.92 vs 7.98 ± 1.92 months, P = .006), and increased respiratory hospitalization risk (relative risk 1.97, 95% CI 1.01-3.85, 0.047), even after adjustment for covariates. Subjects receiving thickening had fewer respiratory hospitalization nights and longer time to supraglottoplasty (9.3 ± 1.7 vs 4.56 ± 0.73 months, P = .004), even after adjustment. Acid suppression use does not reduce the frequency of supraglottoplasty and related hospitalizations compared with untreated subjects. However, patients treated with thickening have decreased hospitalization and longer time to supraglottoplasty, suggesting that thickening of feeds may be a preferred intervention over acid suppression.